Breakfast Consumption and Academic Achievement Among Chinese Adolescents: A Moderated Mediation Model - Gao, Chun Lei; Zhao, Nan; Shu, Ping (Frontiers in Psychology, 2021)
The studies have shown that a healthy lifestyle has a significant impact on the academic achievement of adolescents. Behavior of breakfast eating is considered a hallmark of dietary patterns and an important component of a healthy lifestyle. The prior study explained that students had a lower level of achievement motivation at school because they were exposed to some militating factors in their families such as absenteeism, ill health, malnutrition, and hunger. This study examined the mediating role of achievement motivation and moderating role of socioeconomic status (SES) in the association between breakfast consumption and academic achievement. This study used a sample of 15-year-old Chinese students who participated in Program for International Student Assessment (PISA) 2015. In terms of gender, female students accounted for 47.2% and male students accounted for 52.8%. The results showed that (1) breakfast consumption had a positive predictive effect on academic achievement; (2) achievement motivation played a partial mediating role in the relationship between breakfast consumption and academic achievement; and (3) the direct and indirect effects were moderated by the SES of students, which meant that the effect of breakfast consumption on achievement motivation can differ depending on the SES of students. Besides, both the effects were stronger for individuals with higher SES. The conclusion of this study has an important theoretical value and reference value to guide the Chinese parents and Chinese adolescents to pay more attention to breakfast consumption and healthy lifestyles.